TEACHING TURKISH GRAMMAR AND SPEAKING TO GERMANS IN GERMANY AROUND 1890S: TÜRKİSCHE KONVERSATİONS-GRAMMATİK COURSEBOOK - ERSOY TOPUZKANAMIŞ (Journal of Ottoman Legacy Studies, 2019)
Understanding the history of teaching Turkish as a foreign language is important to explore methods, techniques, and materials used in the historical process and the way Turkish grammar was depicted. For this reason, coursebooks are the fundamental sources to be investigated. This study aims to investigate Türkische Konversations-Grammatik book written by Heinrich Jehlitschka who was born in Vienna in 1861. The research adopted document analysis method, and 1895 and 1897 editions of the book which comprised of two volumes were utilized. Following the introduction of available author information, the contents of the book was presented in turn. The first volume of the book was organized in two sections; first of which included Turkish elements, and the second section contained Arabic and Persian components. The second volume, on the other hand, served as an answer key, including translations of the texts in the first volume and some detailed information about official correspondence. It is intriguing that, in the first volume, the author offered example texts and translation exercises for each grammar topic. To add, the book focused on developing writing and reading skills. The book is significant since it reflects the Turkish language of the time period in terms of the grammar topics chosen by the author.